Kurangnya Kesadaran Masyarakat Untuk Uji Kendaraan Bermotor : Penyebab dan Akibat - Novia Putri Romadhoni (Journal of Student Research, 2023)
The public’s lack of understanding of the benefits of vehicle testing and driving safety can have serious impacts on road safety and the environment. Many vehicle owners do not realize that vehicle testing is not only a legal obligation, but is also a preventive step that can reduce the risk of accidents and extend the service life of the vehicle. Efforts to increase public awareness need serious attention from the government, educational institutions and non-governmental organizations. The aim of this writing is to raise public awareness about motor vehicle testing. The method used in this research is Literature Review. The literature review method is a description of theories, findings and other research materials obtained from reference materials to serve as a basis for research activities. Literature reviews contain reviews, summaries and the author’s thoughts about several library sources (articles, books, slides, information from the internet, etc.) about the topic being discussed. The research results show that by exploring the causes and consequences of this lack of awareness, strategic steps can be taken to increase public understanding and compliance with vehicle testing procedures. The government, educational institutions and other related parties need to work together to create a safer and more sustainable environment on Indonesian roads. In this context, education and outreach are the main keys to changing society’s paradigm regarding the importance of motor vehicle testing.